PENGARUH KECERDASAN INTELEKTUAL DAN SPIRITUAL TERHADAP KINERJA MELALUI MOTIVASI DAN KEPUASAN KERJA PEGAWAI KPP PRATAMA JEMBER - Robbil, Fani Alifah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The purpose of this study were to determine the effect of intellectual and spiritual intelligence on the performance through motivation and job satisfaction at Kantor Pelayanan Pajak Pratama Jember. This study included explanatory research with quantitative method. The population in this study were all employees of the KPP Pratama Jember number 102 employeesThe variables of this research were the intellectual, spiritual intelligence, motivation, job satisfaction and performance. The results showed that the Intelligence intellectual had significant effect employee motivation KPP Pratama Jember. Intelligence spiritual had significant effect employee motivation KPP Pratama Jember. Intellectual had no significant effect on employee job satisfaction of employees KPP Pratama Jember. Intelligence spiritual had significant effect on employee satisfaction KPP Pratama Jember. Intellectual acumen has no significant effect on employee performance KPP Pratama Jember. Intelligence spiritual had significant effect employee performance KPP Jember. Motivation effect on employee satisfaction KPP Pratama Jember. Employee satisfaction had significant effect employee performance KPP Pratama Jember.Keywords: Intellectua Lintelligence, Spiritual Intelligence, and Performance.